Quality Analysis and Comprehensive Evaluation of Dongxiang Blue-Shelled Eggs at Different Laying Stages - XIE Min, GONG Lihui, GUANG Yelan, FEI Dan, ZHOU Yaomin, XU Jun (Shipin Kexue)
To investigate the changes in the quality of Dongxiang blue-shelled eggs at different laying stages, the egg quality, nutrient composition and mineral element contents were measured at the early (22 weeks old), middle (39 weeks old) and late laying phases (62 weeks old). At the same time, principal component analysis (PCA) and fuzzy membership function (FMF) analysis were employed to comprehensively evaluate the quality of eggs. The results showed that the egg quality, nutrient components and mineral elements varied to different extents with laying age. All quality indexes except b* value and the contents of magnesium (P > 0.05) changed significantly across the three laying phases (P early > late. The results of this study provide a reference for establishing quality standards and evaluation methods for local eggs.